2015
DOI: 10.1080/15384101.2015.1093707
|View full text |Cite
|
Sign up to set email alerts
|

Direct reprogramming of human fibroblasts into sweat gland-like cells

Abstract: These authors contributed equally to this work.Keywords: fibroblast, Lef-1, NF-kB, reprogramming, regeneration, sweat glands Abbreviations: CEA, carcinoembryonic antigen; CK7, cytokeratin 7; CK14, cytokeratin 14; CK19, cytokeratin 19; DMEM, Dulbecco's modified Eagle's medium; FBS, fetal bovine serum; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; Lef-1, lymphoid enhancer-binding factor 1; min, minutes; NF-kB, nuclear factor kappa-light-chain-enhancer of activated B cells; Shh, sonic hedgehogThe skin of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The initial report of reprogrammed human fibroblasts, transplanted into the paws of mice with full thickness scald injuries becoming functional sweat gland cells, is an interesting development of the findings that sweat gland cells contribute to wound healing. However, these results require further investigation, as it is not yet clear whether the detected sweat gland cells were derived from incomplete removal of glands from the host or truly derived from the transplanted fibroblasts.…”
Section: Regnerating Sweat Glandsmentioning
confidence: 99%
“…The initial report of reprogrammed human fibroblasts, transplanted into the paws of mice with full thickness scald injuries becoming functional sweat gland cells, is an interesting development of the findings that sweat gland cells contribute to wound healing. However, these results require further investigation, as it is not yet clear whether the detected sweat gland cells were derived from incomplete removal of glands from the host or truly derived from the transplanted fibroblasts.…”
Section: Regnerating Sweat Glandsmentioning
confidence: 99%
“…Many methods have been used for skin repair, such as stem cell injection and somatic cells reprogramming for tissue regeneration. 26 However, efficacious and safe treatments to repair photo-injured skin need further research. In this study, CDSC-CNM has shown efficient regenerative and reparative effects on UVB-irradiated keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent research suggested that the human keratinocyte growth factor played a pivotal role in promoting hucMSC differentiation to sweat gland-like cells [95]. The first transgenic report transformed the key factors NF-kb and Lef-1 that were related to sweat gland development and directly reprogrammed fibroblasts into sweat gland-like cells [96]. However, no study reported on how to use bioactive molecules alone to obtain the SGCs, which needed further exploration.…”
Section: Hair Follicle Cells Derived By Bioactive Moleculementioning
confidence: 99%